2000
DOI: 10.1007/s003600000115
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on Na-dependent Pi transport in ovine, caprine and porcine renal cortex

Abstract: In contrast to monogastric species, renal excretion of inorganic phosphate (Pi) in ruminants is low and this could be attributed to an almost complete tubular Pi reabsorption. However, the functional and regulatory basis for this phenomenon has not yet been clarified. Therefore, it was the aim of the present study to characterize the kinetic parameters of the tubular Pi reabsorption system as affected by P or Ca depletion using preparations of renal cortex brush border membrane vesicles (BBMV) from goats and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Interestingly, a stimulation of NaPi IIa expression was accomplished by dietary protein reduction and thereby, presumably, a reduction in P i in the ultrafiltrate. A direct dietary P i depletion without manipulation of GFR did not show the same effects (Schröder et al, 2000).…”
Section: Renal Handling Of Phosphorusmentioning
confidence: 89%
See 2 more Smart Citations
“…Interestingly, a stimulation of NaPi IIa expression was accomplished by dietary protein reduction and thereby, presumably, a reduction in P i in the ultrafiltrate. A direct dietary P i depletion without manipulation of GFR did not show the same effects (Schröder et al, 2000).…”
Section: Renal Handling Of Phosphorusmentioning
confidence: 89%
“…The uptake of filtered P i at the apical side is mediated by Na þ -dependent P i transporters: electrogenic NaPi IIa (SLC34A1) and electroneutral NaPi IIc (SLC34A3) in both ruminant and non-ruminant species (Figure 7) (Biber and Murer, 1994;Shirazi-Beechey et al, 1996;Huber et al, 2003;Starke et al, 2013). Ovine and caprine amino acid sequence, kinetic and stoichiometric parameters of renal cortex Na þ -dependent P i transport are comparable to the type IIa Na þ /P i co-transport in monogastric species (Schröder et al, 2000). Basolateral P i extrusion mechanism is still unknown.…”
Section: Renal Handling Of Phosphorusmentioning
confidence: 92%
See 1 more Smart Citation
“…Plasma uric acid concentrations in horses increase with intense exercise [ 34 ] and endurance exercise [ 35 ], and perhaps high renal NPT1 expression may assist the horse with removal of uric acid produced during exercise. Similarly, a study examining the kinetic parameters of sodium-phosphate co-transporter IIa in sheep and goats found that dietary phosphorus or calcium deficiency did not alter NPT2a transport capacity or affinity [ 36 ]. The authors suggested that PTH-independent pathways for phosphorus reabsorption may be important in the kidneys of ruminants, perhaps suggesting a role for NPT1 in renal tubular phosphate transport in sheep and goats.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with swine, the Na-dependent P transporter has higher and K m (Schroder et al 2000). Furthermore, the plasma Pi concentration that reaches the maximal tubular reabsorptive rate (Tm) is 3 to 4 times above the normal physiological range, which explains that 99% filtered Pi is reabsorbed (Widiyono et al 1998).…”
Section: Cellular Mechanism Of Pi Reabsorptionmentioning
confidence: 99%